Unlearned responses of chicks, Gallus gallus domesticus, towards aposematic insect-like stimuli - Christopher H. Taylor; David J.G. Watson; Francis Gilbert; David J. Pritchard; John Skelhorn; Tom Reader (Animal Behaviour, 2026)

The Decline and Impending Collapse of the Atlantic Salmon ( Salmo salar ) Population in the North Atlantic Ocean: A Review of Possible Causes - Michael Dadswell; Aaron Spares; Jeffrey Reader; Montana McLean; Tom McDermott; Kurt Samways; Jessie Lilly (Reviews in Fisheries Science & Aquaculture, 2022)

Solving sampling bias problems in presence–absence or presence‐only species data using zero‐inflated models - Victoria Nolan; Francis Gilbert; Tom Reader (Journal of Biogeography, 2022)
Aim Large databases of species records such as those generated through citizen science projects, archives or museum collections are being used with increasing frequency in species distribution modelling (SDM) for conservation and land management. Despite the broad spatial and temporal coverage of the data, its application is often limited by the issue of sampling bias and consequently, zero inflation; there are more zeros (which are potentially ‘false absences’) in the data than expected. Here, we demonstrate how pooling species presence data into a ‘pseudo‐abundance’ count can allow identification and removal of sampling bias through the use of zero‐inflated (ZI) models, and thus solve a common SDM problem. Location All locations Taxon All taxa Methods We present the results of a series of simulations based on hypothetical ecological scenarios of data collection using random and non‐random sampling strategies. Our simulations assume that the locations of occurrence records are known at a high spatial resolution, but that the absence of occurrence records may reflect under‐sampling. To simulate pooling of presence–absence or presence‐only data, we count occurrence records at intermediate and coarse spatial resolutions, and use ZI models to predict the counts (species abundance per grid cell) from environmental layers. Results ZI models can successfully identify predictors of bias in species data and produce abundance prediction maps that are free from that bias. This phenomenon holds across multiple spatial scales, thereby presenting an advantage over presence‐only SDM methods such as binomial GLMs or MaxEnt, where information about species density is lost, and model performance declines at coarser scales. Main Conclusions Our results highlight the value of converting presence–absence or presence‐only species data to ‘pseudo‐abundance’ and using ZI models to address the problem of sampling bias. This method has huge potential for ecological researchers when using large species datasets for research and conservation.

Growth impacts in a changing ocean: insights from two coral reef fishes in an extreme environment - Daniele D’Agostino; John A. Burt; Veronica Santinelli; Grace O. Vaughan; Ashley M. Fowler; Tom Reader; Brett M. Taylor; Andrew S. Hoey; Geórgenes H. Cavalcante; Andrew G. Bauman; David A. Feary (Coral Reefs, 2021)
Determining the life-history consequences for fishes living in extreme and variable environments will be vital in predicting the likely impacts of ongoing climate change on reef fish demography. Here, we compare size-at-age and maximum body size of two common reef fish species ( Lutjanus ehrenbergii and Pomacanthus maculosus ) between the environmentally extreme Arabian/Persian Gulf (‘Arabian Gulf’) and adjacent comparably benign Oman Sea. Additionally, we use otolith increment width profiles to investigate the influence of temperature, salinity and productivity on the individual growth rates. Individuals of both species showed smaller size-at-age and lower maximum size in the Arabian Gulf compared to conspecifics in the less extreme and less variable environment of the Oman Sea, suggesting a life-history trade-off between size and metabolic demands. Salinity was the best environmental predictor of interannual growth across species and regions, with low growth corresponding to more saline conditions. However, salinity had a weaker negative effect on interannual growth of fishes in the Arabian Gulf than in the Oman Sea, indicating Arabian Gulf populations may be better able to acclimate to changing environmental conditions. Temperature had a weak positive effect on the interannual growth of fishes in the Arabian Gulf, suggesting that these populations may still be living within their thermal windows. Our results highlight the potential importance of osmoregulatory cost in impacting growth, and the need to consider the effect of multiple stressors when investigating the consequences of future climate change on fish demography.

The Ancient Tree Inventory: a summary of the results of a 15 year citizen science project recording ancient, veteran and notable trees across the UK - Victoria Nolan; Tom Reader; Francis Gilbert; Nick Atkinson (Biodiversity and Conservation, 2020)
Ancient, veteran and notable trees are ecologically important keystone organisms and have tangible connections to folklore, history and sociocultural practices. Although found worldwide, few countries have such a rich history of recording and treasuring these trees as the UK, with its extensive Royal and aristocratic land ownership, unique land management methods and long-standing interest in natural history and species record collecting. As a result, the UK has collated an extensive database of ancient, veteran and notable trees called the Ancient Tree Inventory (ATI). The ATI is the result of a successful, long-term citizen science recording project and is the most comprehensive database of ancient and other noteworthy trees to date. We present here the first review of the ATI in its entirety since its initiation in 2004, including summaries of the UK ancient, veteran and notable tree distributions, the status and condition of the trees, and key information about the recording process and maintenance of the database. Statistical analysis of components of the dataset, comprising 169,967 tree records, suggest there are significant differences in the threats, size, form and location of different types of trees, especially in relation to taxonomic identity and tree age. Our goal is to highlight the value of the ATI in the UK, to encourage the development of similar ancient tree recording projects in other countries, and to emphasise the importance to conservation of continued efforts to maintain and expand databases of this kind.

Spatial and seasonal patterns of communal latrine use by spotted hyenas (Crocuta crocuta) reflect a seasonal resource defense strategy - Jessica D. Vitale; Neil R. Jordan; Geoffrey D. Gilfillan; J. W. McNutt; Tom Reader (Behavioral Ecology and Sociobiology, 2020)

The influence of thermal extremes on coral reef fish behaviour in the Arabian/Persian Gulf - Daniele D’Agostino; John A. Burt; Tom Reader; Grace O. Vaughan; Ben B. Chapman; Veronica Santinelli; Geórgenes H. Cavalcante; David A. Feary (Coral Reefs, 2020)

Extinction risk and conservation gaps for Aloe (Asphodelaceae) in the Horn of Africa - Steven P. Bachman; Paul Wilkin; Tom Reader; Richard Field; Odile Weber; Inger Nordal; Sebsebe Demissew (Biodiversity and Conservation, 2020)
Identification of conservation priorities is essential for conservation planning, especially as the biodiversity crisis develops. We aimed to support conservation prioritisation by addressing knowledge gaps for the genus Aloe in the Horn of Africa. Specifically, we developed a dataset of herbarium voucher specimens and occurrence data to estimate geographic distribution of 88 species of Aloe and used this to estimate extinction risk and establish the major threats to Aloe in this region. The resulting assessments, each published on the IUCN Red List, show that 39% of the species are threatened with extinction, and the principal threats are the expansion and intensification of crop farming and livestock farming, gathering of plants, and unintentional effects of logging and wood harvesting. We review ex situ conservation in botanic gardens and seed banks, revealing gaps in coverage and urgent priorities for collection, with 25 threatened Aloe species currently unrepresented in seed banks. Protected areas in the region offer limited coverage of Aloe distributions and the most recently designated protected areas are increasingly in regions that do not overlap with Aloe distributions. However, we show with a simple optimisation approach that even a modest increase in protected area of 824 square kilometres would allow representation of all Aloe species, although further data are needed to test the area required to ensure long-term persistence (resilience) of Aloe species.

Hoverflies are imperfect mimics of wasp colouration - Christopher H. Taylor; Tom Reader; Francis Gilbert (Evolutionary Ecology, 2016)

Live-trapping in the stalk zone of tall grasses as an effective way of monitoring harvest mice (Micromys minutus) - Esther F. Kettel; Martin R. Perrow; Tom Reader (European Journal of Wildlife Research, 2016)

Phenotypic heterogeneity is a selected trait in natural yeast populations subject to environmental stress - Sara L. Holland; Tom Reader; Paul S. Dyer; Simon V. Avery (Environmental Microbiology, 2014)
Summary Populations of genetically uniform microorganisms exhibit phenotypic heterogeneity, where individual cells have varying phenotypes. Such phenotypes include fitness‐determining traits. Phenotypic heterogeneity has been linked to increased population‐level fitness in laboratory studies, but its adaptive significance for wild microorganisms in the natural environment is unknown. Here, we addressed this by testing heterogeneity in yeast isolates from diverse environmental sites, each polluted with a different principal contaminant, as well as from corresponding control locations. We found that cell‐to‐cell heterogeneity (in resistance to the appropriate principal pollutant) was prevalent in the wild yeast isolates. Moreover, isolates with the highest heterogeneity were consistently observed in the polluted environments, indicating that heterogeneity is positively related to survival in adverse conditions in the wild. This relationship with survival was stronger than for the property of mean resistance ( IC 50 ) of an isolate. Therefore, heterogeneity could be the major determinant of microbial survival in adverse conditions. Indeed, growth assays indicated that isolates with high heterogeneities had a significant competitive advantage during stress. Analysis of yeasts after cultivation for ≥ 500 generations additionally showed that high heterogeneity evolved as a heritable trait during stress. The results showed that environmental stress selects for wild microorganisms with high levels of phenotypic heterogeneity.

Effect of characteristics of butterfly species on the accuracy of distribution models in an arid environment - Tim Newbold; Tom Reader; Samy Zalat; Ahmed El-Gabbas; Francis Gilbert (Biodiversity and Conservation, 2009)

Climate‐based models of spatial patterns of species richness in Egypt’s butterfly and mammal fauna - Tim Newbold; Francis Gilbert; Samy Zalat; Ahmed El‐Gabbas; Tom Reader (Journal of Biogeography, 2009)
Aim Identifying areas of high species richness is an important goal of conservation biogeography. In this study we compared alternative methods for generating climate‐based estimates of spatial patterns of butterfly and mammal species richness. Location Egypt. Methods Data on the occurrence of butterflies and mammals in Egypt were taken from an electronic database compiled from museum records and the literature. Using M axent , species distribution models were built with these data and with variables describing climate and habitat. Species richness predictions were made by summing distribution models for individual species and by modelling observed species richness directly using the same environmental variables. Results Estimates of species richness from both methods correlated positively with each other and with observed species richness. Protected areas had higher species richness (both predicted and actual) than unprotected areas. Main conclusions Our results suggest that climate‐based models of species richness could provide a rapid method for selecting potential areas for protection and thus have important implications for biodiversity conservation.

Inter-Order Interactions Between Flower-Visiting Insects: Foraging Bees Avoid Flowers Previously Visited by Hoverflies - Tom Reader; Ian MacLeod; Philip T. Elliott; Oliver J. Robinson; Andrea Manica (Journal of Insect Behavior, 2005)